Achieving the paradox of concurrent internationalization speed: Internationalizing rapidly in both breadth and depth - Batsakis, Georgios; Theoharakis, Vasilis (Springer, 2021)
In this paper, we draw on the notions of breadth and depth of internationalization speed in an attempt to examine the performance implications for multinational enterprises (MNEs) that rapidly and concurrently internationalize in new and existing foreign markets. Specifically, we examine the organizational paradox which suggests that firms which grow internationally by concurrently expanding rapidly in both new foreign markets (breadth) and in foreign markets they currently operate (depth), are better off than firms which do not adopt such an approach. Since past research has not examined the interaction between the breadth and depth of MNE internationalization speed on firm performance, we contribute to the temporal dimension of the internationalization process by developing a novel, yet paradoxical approach. Our analysis is based on a longitudinal sample of the world’s largest retail MNEs covering the period 2003 – 2012, which includes the 2008 financial crisis that had a significant effect on the global economy. We find that concurrent internationalization speed positively relates to firm performance during periods of stability. Further, we draw from the upper-echelons theory and find that the aforementioned relationship can be strengthened by the level of CEO international experience and CEO education.
Keywords: Firm performance; upper echelons theory; paradox theory; depth of internationalization speed; breadth of internationalization speed; Concurrent internationalization speed